The Readiness of Teachers in Secondary Schools in Kuwait to Employ the Ethics and Values of the Fourth Industrial Revolution - Nayef AlMutairi; Eman Alharbi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the degree to which secondary school teachers in the State of Kuwait possess the ethics and values of the Fourth Industrial Revolution. A descriptive approach was used, where a 20-item questionnaire consisting of three domains was developed (school administration, teachers, and students). The questionnaire was then distributed to the study sample consisting of (89) teachers in the State of Kuwait. The results of the study showed that the degree to which secondary school teachers in the State of Kuwait possess the ethics and values of the Fourth Industrial Revolution came to a high degree, with an average of (3.80). The results showed that there were no statistically significant differences in the estimates due to gender, educational qualification or experience. The researcher recommends holding more specialized training courses and workshops in the field of modern technology and the Fourth Industrial Revolution for teachers.